2022
DOI: 10.1186/s12957-022-02793-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and a nomogram model for postoperative delirium in elderly gastric cancer patients after laparoscopic gastrectomy

Abstract: Background To evaluate the risk factors of postoperative delirium (POD) in elderly gastric cancer (GC) patients after laparoscopic gastrectomy and construct a predictive model. Methods Elderly GC patients undergoing laparoscopic gastrectomy were enrolled and grouped based on the status of POD development within postoperative 7 days. Independent risk factors were selected out by univariate and multivariate logistic regression analyses and then enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Similarly, related research has demonstrated that AFR can predict the prognoses of patients with pancreatic cancer[ 51 ], gallbladder cancer[ 59 ], and colorectal cancer[ 60 ]. Chen et al [ 61 ] reported that AFR was a distinct risk factor for postoperative delirium in senior gastric cancer patients who underwent laparoscopic gastrectomy, with a cut-off value of 9.95 and an AUC area of 0.614. You et al [ 25 ] found that major postoperative complications in senior gastric cancer patients after laparoscopic radical gastrectomy were predicted by the preoperative AFR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, related research has demonstrated that AFR can predict the prognoses of patients with pancreatic cancer[ 51 ], gallbladder cancer[ 59 ], and colorectal cancer[ 60 ]. Chen et al [ 61 ] reported that AFR was a distinct risk factor for postoperative delirium in senior gastric cancer patients who underwent laparoscopic gastrectomy, with a cut-off value of 9.95 and an AUC area of 0.614. You et al [ 25 ] found that major postoperative complications in senior gastric cancer patients after laparoscopic radical gastrectomy were predicted by the preoperative AFR.…”
Section: Discussionmentioning
confidence: 99%
“…An advanced age has been widely accepted as a major demography-related preoperative risk factor affecting the onset of POD in several studies [41][42][43][44]. As the increase of age, degeneration of compensatory physiological mechanisms and organ function, remarkably reduced body adaptability to drastic alterations during the surgical period leaded to a signi cantly increased risk of POD [29]. In addition, the older patients may be associated with brain atrophy, gradual neurodegeneration, decreased cerebral neurotransmitters production, the narrowing of cerebral vessels due to endothelial dysfunction and atherosclerosis, making older patients more susceptible to POD [45,46].…”
Section: Development and Validation Of Nomogram Modelmentioning
confidence: 99%
“…Therefore, it is crucial to develop an individual predictive model and early identi cation of patients at high risk for delirium. In recent years, some prediction models of POD had been established in hip replacement [23,24], laparoscopic surgery for gynecologic cancers [25], thoracic endovascular aortic repair[26], cardiovascular surgery [27], free ap reconstruction for head and neck cancer[28] and laparoscopic gastrectomy [29]. However, the predictive effect of each prediction model differ sharply, and there is no model to predict the risk of POD in esophageal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…ICRs have been also investigated in various disorders of the central nervous system, such as delirium, Parkinson’s disease, Alzheimer’s disease, multiple sclerosis, and schizophrenia [ 42 , 43 , 44 , 45 , 46 ]. Regarding affective disorders, it was not until 2015, when Demir et al and Cakir et al first investigated NLR in MDD and BD respectively, and both reported higher levels of NLR in MDD and BD patients compared to healthy controls [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%